Experimental Investigations on a Four Stroke Compression Ignition Engine Using Neat Tobacco Seed Oil as an Alternate Fuel (Global Journals of Research in Engineering, 2013)
Performance, emission and combustion tests were carried out on a four stroke compression ignition engine using tobacco seed oil by varying fuel injection pressure and fuel injection timing and compared with base line diesel. The main objective of conducting the performance test on a most widely used agricultural segment engine with tobacco seed oil to help the farming community to use tobacco seed oil in case of emergency and short term applications. At 260 Bar and 26#xB0; BTDC the performance of the engine is quite encouraging compared to the operation of the engine at standard injection pressure of 205 bar and 23#xB0; BTDC
Keywords: compressed air motor (cam)/ pneumatic wrench; compressed air technology; ecofriendly; global conditions; renewable energy handling